Characterization of a flavonol‐rich antioxidant fraction from Spondias purpurea L. pulp and the effect of its incorporation on cellulose acetate‐based film. (11th December 2020) - Vasconcelos, Ludimilla Adorno; Reis, Letícia Caribé Batista; Dias, Êuder Reis; Camilloto, Geany Peruch; Branco, Alexsandro
Abstract: BACKGROUND: Active packaging containing natural flavonoid has recently emerged as a result of its potential to inhibit the oxidation of foods by interacting with it and/or its surrounding environment, with the aim of counteracting oxidation reactions and extending the shelf‐life of foods. The plant Spondias purpurea L. is widely found in northeastern Brazil and is known to contain bioactive flavonoids. The present study aimed to obtain a flavonoid‐rich fraction from the pulp of S. purpurea L. and incorporate it into the cellulose acetate film to obtain biodegradable films with antioxidant properties. RESULTS: The fractionation in SiO2 open‐column chromatography of the S. purpurea pulp crude extract furnished an antioxidant active fraction containing the flavonols quercetin 3‐ O ‐rutinoside and kaempferol 3‐ O ‐rutinoside as the major compounds. This active fraction was incorporated (10, 20 and 30 g kg −1 ) into the substance produced with the casting method for cellulose acetate films. The films produced were characterized concerning mechanical properties, water vapor permeability (WVP) and antioxidant activity. CONCLUSION: The incorporation of the active flavonoid fraction from S. purpurea in the cellulose acetate films decreases WVP and elongation at break, at the same time as increasing antioxidant activity, tensile strength and elastic modulus. Thus, the S. purpurea pulps may be an alternative as a source of antioxidants for use in cellulose acetate films. © 2020 Society of Chemical Industry